Quality of Intra-Hospital Nutritional Counseling in Patients with STEMI in the Public and Private Health Networks of Sergipe: The VICTIM Register - Lima, Ticiane Clair Remacre Munareto; Silva, Danielle Góes da; Barreto, Ikaro Daniel de Carvalho; Oliveira, Jussiely Cunha; Oliveira, Laís Costa Souza; Arcelino, Larissa Andreline Maia; Oliveira, Jeferson Cunha; Sousa, Antônio Carlos Sobral; Barreto Filho, José Augusto Soares (Arquivos brasileiros de cardiologia, 2019)
Having appropriate dietary habits is part of the recommendations after ST-Elevation Myocardial Infarction (STEMI), however, the quality of intra-hospital nutritional counselling in the different health services has been minimally explored. To evaluate the quality of intra-hospital nutritional counselling among patients with STEMI in the public and private health systems in Sergipe. A cross-sectional, with data from the Via Crucis for the Treatment of Myocardial Infarction (VICTIM) Register, conducted from April to November of 2017, with individuals aged ≥ 18 years diagnosed with STEMI, in one public health service hospital and three private hospitals. The occurrence and quality of nutritional counselling were analyzed based on current guidelines and the administration of questionnaires. A significance level of 0.05 was adopted. A total of 188 patients were analyzed; 80.3% were from the public health service facility. Among the interviewees, 57.6% of the public health service, and 70.3% of the private hospital patients received intra-hospital nutritional counselling (p = 0.191). The documentation of this practice, in medical records, was lower in the public service (2.6% vs. 37.8%, p < 0.001). A predominance of restrictive orientations was found in the public and private sectors, mainly regarding salt and fat, 52.3% and 70.3% respectively (p = 0.064). Patients from the private service were more counselling to introduce of cardioprotective foods, mainly fruit, vegetable/legume consumption (48.6% vs. 13.2%, p < 0.001). Among those who received counselling, nutritional knowledge was higher in the private sector (68.2% vs. 26.3%, p < 0.001). The intra-hospital nutritional counselling provided to patients with STEMI, in Sergipe, still presents poor quality in both services, especially in the public health system.